The Effect of Price and Service Quality on Consumer Satisfaction - Wulandari, Agni Audia; Akbar, Aldrin; Lina, Ros (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study aims to explore and understand the impact of price and service quality on customer satisfaction in the photocopy service sector, specifically Photocopy Agung Center in Jayapura City. Research Design and Methodology: The research employed a quantitative survey with 200 respondents who had used photocopy services more than twice in the past three months. Data was collected through a questionnaire comprising three main sections: respondent demographics, perceptions of price and service quality, and customer satisfaction. The validity and reliability of the questionnaire were tested through a pilot test with 30 respondents and statistical analysis using SPSS 29. Data analysis involved multiple linear regression to assess the impact of price and service quality on customer satisfaction. Findings and Discussion: The results indicate that price and service quality significantly influence customer satisfaction, with service quality having a more dominant impact. The study also reveals that certain aspects of service quality, such as reliability and empathy, have a more significant effect on customer satisfaction. Implications: The findings underscore the importance of maintaining competitive pricing and continuously improving service quality to enhance customer satisfaction and loyalty. The study recommends further in-depth and comparative research across different service sectors.